The Strategy To Enrich Graduated Law Student In Order To Face 4.0 Industrial Era - Santoso, Heri (Fakultas Hukum Universitas Kadiri, 2019)
In the era of the industrial revolution, law graduates are demanded by the public to have work readiness and readiness to solve legal problems. Legal problems can only be solved by law graduates who have specific competency legal skills. So that legal education institutions need a teaching strategy, curriculum and educational methods to produce competent law graduates. In this study, a qualitative method is used with a descriptive design, namely research that provides an accurate description of a particular individual or group about the circumstances and symptoms that occur. The results of this research that can be found are legal education strategies oriented to practical subjects, focusing on student majors in the fields of criminal, civil, agrarian and business law, supported by the role of law laboratories that support student practical activities in accordance with their field of legal science concentration. Keywords: Strategy, Faculty of Law, Specific Competencies